2010
DOI: 10.1016/j.nbd.2010.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun kinase provides neuroprotection in a model of Alzheimer's disease

Abstract: The c-Jun N-terminal kinase (JNK) pathway potentially links together the three major pathological hallmarks of Alzheimer’s disease (AD): development of amyloid plaques, neurofibrillary tangles, and brain atrophy. As activation of the JNK pathway has been observed in amyloid models of AD in association with peri-plaque regions and neuritic dystrophy, as we confirm here for Tg2576/PSM146L transgenic mice, we directly tested whether JNK inhibition could provide neuroprotection in a novel brain slice model for amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…The basal levels of pJNK1-3 were nominally higher in ␣4␤2-nAChR-transfected cells as compared with mock-transfected cells. This up-regulation is consistent with the recent studies demonstrating the neuroprotective effect of inhibiting JNK activity in rodent AD models (26,27).…”
Section: Differential Activation Of Mapk Pathways Following Sustainedsupporting
confidence: 92%
See 1 more Smart Citation
“…The basal levels of pJNK1-3 were nominally higher in ␣4␤2-nAChR-transfected cells as compared with mock-transfected cells. This up-regulation is consistent with the recent studies demonstrating the neuroprotective effect of inhibiting JNK activity in rodent AD models (26,27).…”
Section: Differential Activation Of Mapk Pathways Following Sustainedsupporting
confidence: 92%
“…Acute-short-term application of A␤, or often a toxic C-terminal fragment of A␤ (A␤ [25][26][27][28][29][30][31][32][33][34][35] ) has been found to activate several signaling pathways (2), including the MAPK cascade (5,6,16,36). Here, we examined the impact of prolonged exposure to A␤ on intracellular signaling in a model cultured nerve cell system (differentiated clonal neuroblastoma cells) selectively expressing ␣4␤2-nAChRs, as defined high-affinity targets for A␤ (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a role of JNK signaling in mediating A␤ toxicity (Morishima et al, 2001), recent studies have demonstrated the neuroprotective effect of inhibiting JNK activity in rodent AD models (Braithwaite et al, 2010;Ramin et al, 2011). Furthermore, JNK-mediated APP phosphorylation at Thr (T) 668 has been proposed as a mechanism to prevent APP degradation and increase A␤ production in a neuroglioma cell line (Colombo et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…24,25,37,38) Therefore, we investigated the effects of P. multiflorum and S. commixta extracts intake on JNK or EGFR activity. As shown in Figs.…”
mentioning
confidence: 99%